(untitled) (Perner’s Contacts, 2011)
This paper focuses on optimizing the temporal position of the connection with regard to uniform distribution connection on section of transport network, which is operated by several lines of public mass transport. This article presents a list of input data that are needed to solve the problem, define appropriate optimization criteria and the mathematical model used to solve the problem. In the conclusion of this paper there is specific application used to verify the functionality of a mathematical model. In the present paper there is shown a mathematical model of one-way time coordination of connection.